Rho GTPase signaling promotes constitutive expression and release of TGF-β2 by human trabecular meshwork cells. (May 2016) - Pervan, Cynthia L.; Lautz, Jonathan D.; Blitzer, Andrea L.; Langert, Kelly A.; Stubbs, Evan B.
Abstract: Elevated intraocular pressure (IOP) is causally implicated in the pathophysiology of primary open-angle glaucoma (POAG). The molecular mechanisms responsible for elevated IOP remain elusive, but may involve aberrant expression and signaling of transforming growth factor (TGF)-β2 within the trabecular meshwork (TM). Consistent with previously published studies, we show here that exogenous addition of TGF-β2 to cultured porcine anterior segments significantly attenuates outflow facility in a time-dependent manner. By comparison, perfusing segments with a TGFβRI/ALK-5 antagonist (SB-431542) unexpectedly elicited a significant and sustained increase in outflow facility, implicating a role for TM-localized constitutive expression and release of TGF-β2. Consistent with this thesis, cultured primary or transformed (GTM3) quiescent human TM cells were found to constitutively express and secrete measurable amounts of biologically-active TGF-β2. Disrupting monomeric GTPase post-translational prenylation and activation with lovastatin or GGTI-298 markedly reduced constitutive TGF-β2 expression and release. Specifically, inhibiting the Rho subfamily of GTPases with C3 exoenzyme similarly reduced constitutive expression and secretion of TGF-β2. These findings suggest that Rho GTPase signaling, in part, regulates constitutive expression and release of biologically-active TGF-β2 from human TM cells. Localized constitutive expression and release of TGF-β2 by TM cells may promote or exacerbate elevation of IOP in POAG. Highlights: Inhibiting constitutive TGF-β2 expression enhances outflow facility in porcine anterior segments. Inhibition of post-translational geranylgeranylation attenuates constitutive TGF-β2 mRNA expression independently of mRNA stability in cultured human TM cells Pharmacological inhibition of the Rho GTPase subfamily significantly reduces constitutive TGF-β2 expression and release in cultured human TM cells